Advance Information and Consumption Insurance: Evidence from Panel Data - Marcelo Pedroni; Swapnil Singh; Christian Stoltenberg (Tinbergen Institute, 2022)
We investigate whether US households possess advance information about their future income and what this means for consumption insurance. Based on insights from a theoretical model, we propose a new test to detect advance information, which requires only panel data on consumption and income. Using the Panel Study of Income Dynamics, we find—in contrast to the existing literature—strong support for the existence of advance information. We use this evidence to estimate a standard incomplete markets model and find that advance information reduces households' income forecast errors by 15%. Our estimation results imply that 27% of all unexpected income changes are passed through to consumption. Ignoring advance information leads to a significant overestimation of consumption insurance and even more so at the bottom of the wealth distribution.
Keywords: C23; D12; D31; D52; D81; E21; G52; 330; income risk; advance information; consumption insurance; panel data; incomplete markets